Burial-Related Compaction Modifies Intrusion-Induced Forced Folds: Implications for Reconciling Roof Uplift Mechanisms Using Seismic Reflection Data - Magee, Craig; Hoggett, Murray; Jackson, Christopher A.-L.; Jones, Stephen M. (Frontiers in Earth Science, 2019)
Space for shallow-level sills and laccoliths is commonly generated by bending and uplift of overlying rock and sediment. This so-called ‘roof uplift’ produces forced folds, the shape and amplitude of which reflect the geometry of underlying intrusions. The surface expression of forced folds can therefore be inverted to constrain intruding magma body properties, whilst ancient forced folds provide a record of sill and laccolith emplacement. Deciphering how shallow-level intrusion translates into roof uplift is thus critical to enhancing our understanding and forecasting of magma emplacement. To-date, emplacement models and surface deformation inversions are underpinned by the consideration that roof uplift is, to a first-order, an elastic process. However, several studies have suggested inelastic processes can accommodate significant magma volumes, implying first-order roof uplift may be a function of elastic and inelastic deformation. In particular, seismic reflection images of forced folds above ancient sills and laccoliths have been used to argue that final fold amplitudes can be substantially less (by up to 85%) than the underlying intrusion thickness. Although these seismic-based observations imply elastic and inelastic deformation accommodated intrusion, these studies do not consider whether burial-related compaction has reduced the original fold amplitude. Here, we use geological (e.g. lithology) and geophysical (e.g. seismic velocity) information from the Resolution-1 borehole offshore eastern New Zealand, which intersects a forced fold and upper ~50 m of a sill imaged in 2D seismic reflection data, to decompact the folded sequence and recover its original geometry. We show the Resolution Sill is likely ~117–187 m thick, depending on the interval velocity for the entire intrusion, whereas the forced fold has an apparent maximum amplitude of ~127 m, corresponding to a sill thickness-fold amplitude discrepancy of up to 47%. Decompaction indicates the original maximum forced fold amplitude likely ranged from ~131–185 m, suggesting post-emplacement, burial-related compaction of this and other forced folds may be the source of apparent discrepancies between fold amplitude and intrusion thickness. Whilst seismic reflection data can provide fundamental insights into how shallow-level emplacement translates into roof uplift and ground displacement, we show decompaction and backstripping are required to recover the original fold geometry.